Survei Pelaksanaan Pembelajaran Pendidikan Jasmani Adaptif SMPLB di Kabupaten Semarang - Ujianita Dhian Nugrohowati; Hermawan Pamot Raharjo (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to determine the process of implementing adaptive physical education learning at SMPLB in Semarang Regency. The method used is descriptive quantitative with a population of 5 SMPLB and the sample used in all adaptive physical education teachers in Semarang Regency is 5 teachers (stratified random sampling). The test instrument uses observation, questionnaires and documentation. The analysis technique used the percentage score formula and the descriptive analysis criteria table percentage from Mohammad Ali in 1993. The results showed (1) the implementation of adaptive physical education learning at SMPLB in Semarang Regency was included in the good category with a percentage of 60%. (2) learning planning for adaptive physical education at SMPLB in Semarang Regency is in the good category with a percentage of 60%. (3) the process of implementing the SMPLB adaptive physical education learning process in Semarang district is included in the very good category with a percentage of 80%. (4) evaluation of adaptive physical education learning at SMPLB in Semarang Regency is included in the good category with a percentage of 80%.. The implementation of adaptive physical education learning at SMPLB in Semarang Regency has been going well, because it has succeeded in preparing and implementing 3 units, namely planning, process, and evaluation in learning.